2002
DOI: 10.1002/mame.200290020
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Copper Oxides on the Curing Behaviors of Bismaleimide Triazine Prepreg

Abstract: The effect of copper oxides on the curing behaviors of the bismaleimide triazine (BT) prepreg is studied with infrared spectroscopy (IR), attenuated total reflection infrared spectroscopy (ATR), and X‐ray photoelectron spectroscopy (XPS). The result of IR analyses indicates that there is a concentration distribution present in the prepreg surface layer and the outer surface layer contains less cyanate, imide, and epoxide but more triazine groups than the inner layer. From ATR, it is concluded that the cuprous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…3b). It shows that the peaks (dotted line indicated) in the BMP-containing cells around 288.4 eV are attributed to the bond from NC¼O in bismaleimide [19,21].…”
Section: Interface Film Formation and Characterizationmentioning
confidence: 95%
“…3b). It shows that the peaks (dotted line indicated) in the BMP-containing cells around 288.4 eV are attributed to the bond from NC¼O in bismaleimide [19,21].…”
Section: Interface Film Formation and Characterizationmentioning
confidence: 95%
“…18 Various different catalytic curing reactions that occur on the copper surface are reported elsewhere also. [19][20][21][22] It was shown previously that the cuprous oxide attracted more cyanate ester but less bismaleimide resins from the prepreg to its surface than the cupric oxide; the copper surface affected the curing extent of the bismaleimide triazine (BT) resin in contact and the effect of cupric oxide was more significant than that of the cuprous oxide. 22 In addition to the effects on the cure, copper could catalyze the degradation reaction of various polymer resins.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that transition metallic ions such as Al +3 show strongly catalytic effects to the polycyclomerization of cyanate ester due to their low coordination number and high ligand mobility during the cure process 9. In addition, some metal oxides, such as ZnO,10 TiO 2 ,11 CuO, Cu 2 O,12 silicate13, 14 also have catalytic effects to the polycyclomerization of cyanate ester. The main components of the HGS are SiO 2 and Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%